Clouclip combined with a questionnaire on the influence factors of myopia in children - Ya Zhang; Ming Su; Yanhua Sun; Liqin Qi; Lifang Gao; Xueya Wu; Yutong Li; Yanli Liu; Wei Li; Minxiao Jin (Frontiers Media S.A., 2023)
PurposeTo evaluate eye use behavior in myopic and non-myopic children objectively using Clouclip M2 device and subjectively using questionnaire and compare the results. The study also aimed to assess the relationships between ocular biometric parameters and refractive status.MethodsClouclip M2 was used in monitoring eye use behavior and visual environment in children aged 9-11 years. The participants were monitored for 7 days. On the eighth day, data stored in the device were collected, relevant eye examination were conducted and survey questionnaire was administered. The paired sample t-test was used to compare the eye use behavior obtained objectively and subjectively. The relationships between ocular biometric parameters and refractive status were assessed using the Pearson's Correlation analysis.ResultsSpherical equivalent refraction was significantly correlated with axial length, axial length to corneal radius, anterior chamber depth, lens thickness, and corneal radius (P < 0.05). The average time per day spent on near work, the maximum time for single near work, and the average near working distance were significantly lower, and the average total time spent on outdoor activities was significantly longer as determined by questionnaire method than that found using Clouclip M2. Logistic regression analysis revealed that prolonged near work, shorter working distance, presence of parental myopia, and lesser outdoor activities were significant risk factors for myopia.ConclusionsThe childhood myopia is influenced by eye use behavior, eye use environment, and parental myopia. Results from this study further support that biometric and optical parameters of the eye determine refractive status. Being an objective method, Clouclip M2 provides an independent eye use behavior data which potentially are more reliable than obtained from subjective method. Our study provided a theoretical basis for myopia prevention and control in clinical practice.